Work duration does not affect cortisol output in experienced firefighters performing live burn drills. (January 2017) - Rosalky, Deena S.; Hostler, David; Webb, Heather E.
Abstract: Work duration may affect firefighters' stress responses. Forty-two firefighters (38 males) performed either 2 (SWD) or 3 (LWD) bouts of simulated fire suppression activity. Salivary cortisol, self-reported fear and anxiety, and perceptual thermal responses were measured. Cortisol was evaluated using area-under-the-curve calculations (Pruessner et al., 2003). Affective responses between the two conditions were compared using T-tests. Pearson product moment correlations were used to analyze the relationships between affect and change in thermal load perception. Cortisol decreased across the protocol in both groups, and no difference was found in cortisol or affect between the groups. Cortisol decreased (F4, 36 = 3.43, p < 0.05) in the SWD group from a mean concentration of 40.93 ± 11.41 nmol/L to 25.07 ± 9.88 nmol/L at the end of the protocol. In the LWD group, the mean cortisol concentration decreased from 42.89 ± 11.83 to 25.07 ± 8.82 at the end of the protocol (F5, 50 = 14.77, p < 0.01). Anxiety increased in the LWD (F4, 72 = 5.11, p = 0.001) but not the SWD group. Fear increased in the SWD (F3, 48 = 14.15, p < 0.001) and LWD group (F4, 60 = 4.47, p < 0.01). The present findings suggests a moderate fear load with firefighting, which appears not to be associated with duration of work bout. Examination of more varied work bout lengths may reveal an association between anxiety and work duration. However, the work bout durations investigated in the current study comprise the range of what is practical from an occupational standpoint and the physiological capabilities of the firefighters.